1981
DOI: 10.1111/j.1365-2621.1981.tb02973.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation, Boning Time and Cooking Method on Beef Roasts

Abstract: Sixteen steer carcasses were selected to study effects of electrical stimulation, boning time and cooking methods on palatability traits, cooking loss and chemical composition of beef biceps femoris muscle. Eight carcasses were electrically stimulated and eight carcasses served as controls. The biceps femoris muscle was removed from one side of each carcass within 2 hr of exsanguination and from the remaining side following a 48-hr chill. Muscles were subdivided and cooked in either a convectional electric or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Cooking loss was affected by boning treatment and salt level with HB roasts having lower cooking losses (19.5%) than cold-boned treatments (21.5%), possibly due to the higher pH of the hotboned treatments, which would contribute to an increased waterholding capacity. Several researchers have reported increased water-holding capacity in hot-boned meat (Hamm, 1982;Griffin et al, 1981;Jones et al, 1986). Also, salt addition generally results in greater water-holding capacity and lowered cooking losses (Schwartz and Mandigo, 1975;Pepper and Smith, 1975;Mandigo, 1982;Brewer et al, 1984;Cordray and Huffman, 1984;Chow et al, 1986;Lamkey et al, 1986).…”
Section: Yield Datamentioning
confidence: 99%
“…Cooking loss was affected by boning treatment and salt level with HB roasts having lower cooking losses (19.5%) than cold-boned treatments (21.5%), possibly due to the higher pH of the hotboned treatments, which would contribute to an increased waterholding capacity. Several researchers have reported increased water-holding capacity in hot-boned meat (Hamm, 1982;Griffin et al, 1981;Jones et al, 1986). Also, salt addition generally results in greater water-holding capacity and lowered cooking losses (Schwartz and Mandigo, 1975;Pepper and Smith, 1975;Mandigo, 1982;Brewer et al, 1984;Cordray and Huffman, 1984;Chow et al, 1986;Lamkey et al, 1986).…”
Section: Yield Datamentioning
confidence: 99%
“…The roasts cooked in a microwave oven had greater (P<O.Ol) cooking losses and higher shear force values than products cooked in an electric oven (Griffin et al 1981 ).…”
Section: The Effect Of Heat On Muscle Structurementioning
confidence: 96%
“…In a study by Griffin et al (1981) to determine the effect of electrical stimulation, hot-boning and cookery method (convectional electric oven vs microwave oven) on beef roasts, it was observed that in the electrically stimulated cooked beef product, sarcomeres were longer but palatability traits, cooking loss and chemical content were not different. The roasts cooked in a microwave oven had greater (P<O.Ol) cooking losses and higher shear force values than products cooked in an electric oven (Griffin et al 1981 ).…”
Section: The Effect Of Heat On Muscle Structurementioning
confidence: 99%
“…OVEN has been shown to decrease cooking time as well as labor and energy costs, but it has not been well accepted by food services and homemakers for cooking beef roasts due to uneven cooking, greater cooking losses, and less palatable meat (Headley and Jacobson, 1960;Kylen et al , 1964;Law et al, 1967;Ream et al, 1974;Drew et al, 1980;Griffin et al, 1981). New recommendations for use of lower power levels and rotation techniques for the microwave oven have improved the final beef roast product along with desirable time and energy savings over other cooking methods (Starrack, 1979;Voris and Van Duyne, 1979;Drew et al, 1980;National Live Stock and Meat Board, 1982).…”
Section: Introduction the Microwavementioning
confidence: 99%